Spatial Analysis of Land Critical Level in Protected Forest Area of Gunung Sirimau Ambon City - Engelina Latumarisa; Rafael M Osok; Rudy Soplanit; Silwanus M Talakua (Universitas Pattimura, 2022)
Protected Forest Area of Sirimau Mountain is located in the administrative area of ​​Ambon City which tends to experience disturbances, in the form of conversion of forest functions to agricultural land. This has the potential to cause land degradation which will lead to critical land. The aims of this study were to determine and map the spatial distribution of land critical levels, describe the relationship between the critical land parameters with the value of critical land, and determine the rehabilitation actions of the critical lands. The study was conducted on 15 sample areas representing 212 land units in the study area, and the spatial distribution of critical land was analyzed using geographic information system (GIS) technology based on DIRJEN BPDAS-PS Regulation Number P.4/V-SET/2013. The results of this study showed that the levels of the critical lands in the study area consist of uncritical (122.38 ha), potential critic (972.04 ha), slightly critic (1055.06 ha), critic (​​1085.26 ha), and very critic (​​4.98 ha). The relationship between the critical land parameters and critical values showed that the dense land cover, lower slope steepness, less erosion, and better land management would reduce the levels of critical land. Critical land rehabilitation is recommended based on land use types. Dry land agriculture and mixed dry land farming should be enriched with an agroforestry system, savanna/grassland land, and shrubs should be reforestated (with an agroforestry system), whereas primary and secondary dry land forests are to be maintained as forests.